Extended duration of thromboprophylaxis for medically ill patients: a systematic review and meta‐analysis of randomised controlled trials. Issue 2 (9th February 2020) - Zayed, Yazan; Kheiri, Babikir; Barbarawi, Mahmoud; Banifadel, Momen; Abdalla, Ahmed; Chahine, Adam; Obeid, Michele; Haykal, Tarek; Yelangi, Anitha; Malapati, Sindhu; Bachuwa, Ghassan; Seedahmed, Elfateh
Abstract: Background: The benefit of extended‐duration thromboprophylaxis in patients hospitalised for acute medical illness beyond hospital stay remains controversial. Aims: To perform a meta‐analysis of randomised controlled trials (RCT) in order to examine the efficacy and safety of extended‐duration anticoagulation for venous‐thromboembolism (VTE) prophylaxis in this high‐risk population. Methods: An electronic database search was conducted to include all RCT comparing between extended‐duration versus short‐duration prophylactic anticoagulation in medically ill patients. The primary efficacy outcome was the composite events of asymptomatic deep vein thrombosis (DVT), symptomatic VTE and death from VTE‐related causes. Results: Five RCT were included totalling 40 124 patients, with a mean age of 71 years and 51% were male. In comparison to standard‐duration therapy, extended‐duration thromboprophylaxis was associated with a significant reduction in the primary efficacy outcome (risk ratio (RR) 0.75; 95% confidence interval (CI) 0.67–0.85; P < 0.01), symptomatic VTE (RR 0.53; 95% CI 0.33–0.84; P < 0.01) and asymptomatic DVT (RR 0.81; 95% CI 0.71–0.94; P < 0.01). However, there were no significant differences between both groups with regard to VTE‐related death (RR 0.81; 95% CI 0.60–1.10; P = 0.18) or all‐cause death (RR 0.97; 95% CI 0.88–1.08; P = 0.64). In contrast, extended‐duration thromboprophylaxis was associated with an increased risk of major bleeding (RR 2.04; 95% CI 1.42–2.91; P < 0.01) and non‐major clinically relevant bleeding (RR 1.81; 95% CI 1.29–2.53; P < 0.01). Conclusions: Among hospitalised medically ill patients, prolonging venous thromboprophylaxis was associated with a decreased risk of composite events of the primary efficacy outcome and increased risk of bleeding with no significant difference in VTE‐related death.